Segurança alimentar, produtividade e qualidade de sementes demamoneira em sistema de policultivo - Milton Miro Willms (2010)
The local production of food and energy, that fosters regional development under various circumstances of arrangements, may be an alternative of emancipating the historically underdeveloped rural population. Based on the low-tech, low income family farmer way of living, in addition to the necessity of getting to know the potential of probable combinations of different crops, an experiment of different castor plant intercrops, based on already established crops, was carried out at São Francisco Settlement. The objective of this study was to verify the production, productivity and quality of seeds of the cultivar IAC Guarani castor plant, in different intercropping with beans, corn and squash, as well as describe the farmers impression over the contribution of treatments regarding productive aspects and its food safety. The experiment was arranged in randomized complete block design (RCBD) with six intercrops and four replications, totaling 24 experimental units. The size of each plot was 32.0 m² (4.0 m x 8.0 m). The strips consisted of three rows of castor plants, 1 meter apart, in which the squash cultivar was 50 cm spaced, triangular shape, between castor plants in the treatments 4 and 5, and an additional row of castor plant, 50 cm spacing, triangular shape, in treatment 6. The hedgerows consisted of five rows of beans planted at a density of 10 plants per meter, in treatments 2 and 5; four rows of beans in the same density, with a central row of corn in treatments 3, 4 and 6. In treatment 1, all the rows were planted 50 cm spacing and seedlings 70 cm diagonally. Squash and castor plant intercrops and single castor plant treatment (treatment 1) were planted in triangle or quincunx. All qualitative variables were submitted to analysis of variance and the treatment averages were compared using the Tukey test, admitting an error of 0,05. There was no significant yield decrease per plant in the intercrops and the spacing 1, 0 m x 0, 5 m regarding the spacing 1, 0 m x 1, 0 m intercrops. IAC Guarani castor plant has good productivity in 1, 0 m x 0, 5 m triangle planting. The intercrops in strips had an average productivity of 1,100 Kg/ha regarding castor plant, and 1, 000 Kg/ha of beans. The physical quality of IAC Guarani castor plants seeds, related to seed size and mass of 1,000 seeds was higher in theintercrops than in the single crops. The germination speed index showed higher results to IAC Guarani castor plants in intercrop treatments over single planting ones. The family farmers of São Francisco Settlement prefer the castor plant intercropping rather than the single crop one. It is possible to produce seeds with higher physical and physiological quality and provide food safety to family farmers with the intercropping system.